Upaya Pengembangan Wisata Kota Tanjungpinang Sebagai Daya Tarik Wisata di Era New Normal - Putri Fistyaning Army (Institut Ilmu Sosial dan Manajemen STIAMI, 2021)
Urban tourism development has promising prospects in the future to be developed in the territory of Indonesia, including in the city of Tanjungpinang, Riau Islands. The city is the center of night activities for both domestic and foreign tourists. The emergence of stereotypes that the attractiveness of Tanjungpinang City Tourism is still lacking when compared to Bintan Regency with all its natural tourist attractions is also a challenge for Tanjungpinang City to be able to further maximize its potential, coupled with the problem of the Covid-19 pandemic which also impacts on the rate of development of Tanjungpinang tourism. This study uses a qualitative descriptive method with no recognition of the population and sample, this is because qualitative research is not intended to make generalizations. Efforts to develop the Tanjungpinang City Tourism Object in the new normal era have been carried out by the local government, especially the Tanjungpinang City Culture and Tourism Office, this effort is made to educate the readiness of tourism actors and the community so that when the tourism situation improves, all parties are ready to facing the new normal era.